Tanggung Jawab Perusahaan Pengangkut DHL Express Terhadap Pengiriman Barang dari Jakarta ke Malang ( Studi Putusan Pengadilan Nomor 733/Pdt.G/2017/PN.JKT.SEL.) - Chriesty Angeline; Siti Nurbaiti (Jurnal Hukum Adigama, 2019)
In a transportation agreement, practice the rights and obligations of the parties are not always fulfilled, because during the process of shipping, sometimes it does not always went well, even there is the package disappearance cases. For example, a case that occurred between the DHL Express transport company and the sender Massayu Chairani who was disadvantage due to the loss of her package that the company agreed to delivered. How the company DHL Express responsibility of the shipping to the sender in transportation from Jakarta to Malang and How the District Court Decision Number 733 / Pdt.G / 2017 / PN.JKT.SEL regarding the responsibility of the shipping company DHL Express to the sender in transportation from Jakarta to Malang continue to make a discussion. The research method used is descriptive normative legal research method, using secondary data and primary data as supporting data with the law approach. The results of research illustrate that DHL Express does not give full responsibility to the sender and the results of judges' decisions that do not grant full compensation claims are also considered not in accordance with Article 91 KUHD and Law Number 22 of 2009 concerning Road Traffic and Transportation in Article 188 and Article 193 paragraph (1). It is recommended that DHL Express give full responsibility to the sender of the goods for transporting goods from Jakarta to Malang and should have a court decision can decide the case more carefully to grant full compensation claims.